INFORMATION AND LEGAL SUPPORT OF DEVELOPMENT OF THE PERSONNEL OF ENTERPRISES - V. Chetveryk (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article considers basic aspects of information and legal support of development of the personnel of enterprises. The legal bases for the business activity of the enterprises in part to increasing professional skill level of the personnel are considered. Relevance of researching of development of the personnel of enterprises is defined. The organizational and methodical principles of information support of development of the personnel of agricultural enterprises are determined. The implementation of the above-mentioned recommendations will enable to react adequately if in the nearest future any changes in the macro- and microenvironment occur.